2010
DOI: 10.1111/j.1526-100x.2009.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Coral Reef Restoration (Bolinao, Philippines) in the Face of Frequent Natural Catastrophes

Abstract: Restoration of coral reefs is generally studied under the most favorable of environmental conditions, a stipulation that does not always reflect situations in the field. A 2-year study (2005)(2006)(2007), employing the "reef gardening" restoration concept (that includes nursery and transplantation phases), was conducted in Bolinao, Philippines, in an area suffering from intense human stressors. This site also experienced severe weather conditions, including a forceful southwesterly monsoon season and three sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 48 publications
2
72
0
2
Order By: Relevance
“…In fact, a recent biological study in the reef identified the abundance near Malilnep channel of blue coral (Heliopora coerulea), a species thought to be tolerant of low salinity and nutrient-rich conditions. Moreover, corals transplanted and nursed as part of reef restoration studies died in certain areas and the researchers partly blamed freshwater seepage [Shaish et al, 2010]; these areas are in fact those with higher resistivity and therefore prone to submarine groundwater discharge. Additionally, nutrient analysis of waters from the reef indicates high nitrate concentrations in the vicinity of the Malilnep channel.…”
Section: Summary Conclusion and Implicationsmentioning
confidence: 99%
“…In fact, a recent biological study in the reef identified the abundance near Malilnep channel of blue coral (Heliopora coerulea), a species thought to be tolerant of low salinity and nutrient-rich conditions. Moreover, corals transplanted and nursed as part of reef restoration studies died in certain areas and the researchers partly blamed freshwater seepage [Shaish et al, 2010]; these areas are in fact those with higher resistivity and therefore prone to submarine groundwater discharge. Additionally, nutrient analysis of waters from the reef indicates high nitrate concentrations in the vicinity of the Malilnep channel.…”
Section: Summary Conclusion and Implicationsmentioning
confidence: 99%
“…The specifically developed tool-box applications of the "gardening" concept have already shown ( [23,27,[31][32][33][34] and unpublished) that active reef restoration may reshape coral reef communities (and associated biota) in such a way that novel reef ecosystems, with novel functionalities that did not exist before, may be developed. Clearly, the function of such novel reef ecosystems could deviate markedly (through elements such as species compositions, biodiversity, engineering capacities, goods and services) from that of existing reef systems; they may still provide the same valuable goods and services to society, or perhaps offer different ones.…”
Section: Active Reef Restoration-the "Gardening" Tenetmentioning
confidence: 99%
“…Global climate changes are expected to impose ever increasing challenges to traditional coral reef maintenance measures, and to novel approaches such as the "gardening" tenet as well [31]. Many aspects of the gardening approach and of active reef restoration are still in their nascent stages [23].…”
Section: The "Gardening" Approach As a Climate Change Impact Mitigatormentioning
confidence: 99%
See 1 more Smart Citation
“…Although there exist studies, e.g. [40] and [53], that have investigated the changes in underwater environment after such events happen, most of them have focused on long-term monitoring and they are not able to explore the effects right after the typhoon. This is mainly due to the impracticability for human operators to monitor the area because of, for instance, the floods coming down from neighboring mountains.…”
Section: Introductionmentioning
confidence: 99%